2015
DOI: 10.4236/ojo.2015.57024
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Mortalities among Orthopaedic and Trauma Admissions in Irrua

Abstract: Background: There are many reports from different parts of the world addressing different aspects of surgical mortality. However, none has been done in this centre as it relates to orthopaedics and trauma admissions. Such data are invaluable to health planning and epidemiological monitoring. Objective: To retrospectively review all mortalities arising from orthopaedics and trauma admission as they present to Irrua specialist Teaching Hospital (ISTH) Irrua from Jan 2005-Dec 2014. Method: Medical records of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
4
1
0
Order By: Relevance
“…Its effect on productivity is also eminent as most of the study participants were employed and in their productive years. The study findings resonate the findings of previous studies conducted in other African orthopedic health settings and geographical locations within Ghana (18 –21). This continuing menace may be due to lack of enforcement of road laws, deplorable states of roads, poor lighting, lack of understanding, and observation of road signs precipitated by low levels of education as observed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Its effect on productivity is also eminent as most of the study participants were employed and in their productive years. The study findings resonate the findings of previous studies conducted in other African orthopedic health settings and geographical locations within Ghana (18 –21). This continuing menace may be due to lack of enforcement of road laws, deplorable states of roads, poor lighting, lack of understanding, and observation of road signs precipitated by low levels of education as observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Majority of the study participants were in their productive years (≤55). This may be closely related to the most common cause of admission found in this study, RTA, since RTAs have been found to be more common in younger populations by most studies (18 –21). A probable explanation for this trend could be because most traumatic incidents occur irrespective of comorbid conditions; increasing age is not directly correlated with these conditions.…”
Section: Discussionsupporting
confidence: 51%
“…From a demographic study of trauma worldwide, it commonly occurs in young productive force with more occurrence in males. 13 14 One-third of the deaths occurred in the age range of 11–40 years, which is similar to the research done in other low and middle-income countries. 1 9 15 Probably, this could be due to the majority of outdoor activities performed by adults and children in low and middle-income countries like Ethiopia, 15 and males are more affected with traumas.…”
Section: Discussionsupporting
confidence: 84%
“…An in-ward crude mortality rate of 1.98 was observed over the study period, similar to a study conducted in Nigeria 18 but slightly lower than two other studies conducted in sub-Saharan Africa 19 and the United Kingdom 20 .…”
Section: Discussionsupporting
confidence: 83%